PENERAPAN MANAJEMEN KEPEMIMPINAN DALAM MENINGKATKAN HAFALAN AL-QURAN SANTRI (Study Kasus pondok Pesantren Darun Hamzanwadi NW Nusa Jaya Kecamatan Manggelewa Kabupaten Dompu) - Haerunisa, Haerunisa; Hakim, Lukmanul (UIN Mataram, 2022)
Abstract: This study aims to determine the application of leadership management in improving the memorization of the Qur'an in students at Darun Hamzanwadi Islamic Boarding School NW Nusa Jaya. In addition, this study also aims to determine the supporting and inhibiting factors in implementing leadership management when improving the memorization of the Qur'an of students at Darun Hamzanwadi Islamic Boarding School, NW Nusa Jaya. This research is motivated by the lack of optimal leadership management in improving the memorization of the Qur'an of students. Based on the research results, Darun Hamzanwadi Islamic Boarding School NW Nusa Jaya has implemented leadership management in memorizing the Qur'an. The application of management concepts which include planning, organizing, actuating, and controlling, there are supporting and inhibiting factors in memorizing the Qur'an including: Supporting factors in improving the quality of memorizing the Qur'an For students, these are: the ideal age, good time management, a comfortable place to memorize. While the inhibiting factors are Internal Factors: (1) Lack of interest and talent (2) Lack of self-motivation (3) Health that is often disturbed (4) Low intelligence. External Factors: (1) Instructors in providing guidance (2) Problems with economic capacity